The mechanical fixation of a cementless conical cup in cortical versus cancellous trapezial bone: an experimental study - Thillemann, Janni K; Dremstrup, Lene; Hansen, Torben B; Stilling, Maiken (The Journal of hand surgery, European volume, 2021)
In a pig bone model mimicking the human trapezium, we assessed the cementless fixation of trapezial cups in cancellous and cortical bone. Thirty-two saddle-shaped pig forefoot bones were prepared for cup fixation. Conical Konos cups (Beznoska, Kladno, Czech Republic) size 9 mm or 10 mm diameter were impacted. Cup migration was evaluated with repeated radiostereometry after intervals of cyclic-load tests. Migration increased for every load-interval up to 750 N and was higher with cancellous bone fixation than with cortical bone fixation. In cancellous bone, 9 mm cups migrated more than 10 mm cups. At the highest load (1050 N), the cumulative implant survival was 88% for 10 mm cups with cortical bone fixation and 13% for 9 mm cups with cancellous bone fixation. We conclude that mechanical fixation of conical Konos cups was better in cortical than in cancellous bone. Our results further suggest that the largest possible cup diameter should be used.
Keywords: Animals; osteoarthritis; Trapeziometacarpal arthroplasty; Prosthesis Design; protézy - design; Acetabulum; prasata; radiostereometry; primary cup fixation; acetabulum; selhání protézy; Trapezium Bone; Czech Republic; Swine; Česká republika; náhrada kyčelního kloubu; Arthroplasty, Replacement, Hip; trapézová kost; zvířata; Prosthesis Failure